Peningkatan Hasil Belajar IPA melalui Penerapan Metode Demonstrasi pada Siswa Sekolah Dasar - Cindra Amelia; Mahluddin; Andi Nurhasanah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aimed to improve the science learning outcomes of third-grade students through the implementation of the demonstration method at SD Negeri 1 Rantau Bayur. The study employed Classroom Action Research (CAR) consisting of two cycles, namely planning, implementation, observation, and reflection. The participants were 21 third-grade students. Data were collected through observation, learning achievement tests, and documentation, then analyzed using descriptive qualitative and quantitative techniques. The findings showed that the demonstration method successfully improved students’ learning outcomes. In the first cycle, only 14 students (66.67%) achieved mastery learning with an average score of 77.14. Reflection on the first cycle indicated that students' participation during learning activities was still limited. Therefore, improvements were made in the second cycle by optimizing demonstration activities, encouraging active student participation, and providing more intensive guidance. The results of the second cycle demonstrated a significant improvement, with all students (100%) achieving mastery learning and an average score increasing to 89.52. Students also became more active in observing, asking questions, discussing, and drawing conclusions during the learning process. The findings indicate that the demonstration method creates meaningful learning experiences that help students understand scientific concepts more effectively. Therefore, the demonstration method is considered an effective instructional strategy to improve elementary school students' science learning outcomes.